Aerobic energy contribution to maximal exercise in children - Chia, Y. H. M. (Biology of Sport, 2006)
The aerobic energy contribution to a 30-s Wingate Anaerobic Test (WAnT30 s) was examined in 18 boys and 18 girls aged 10-12 years. Participants completed an incremental test to volitional exhaustion to determine peak oxygen uptake (VO2) and a WAnT30 s °n two separate occasions on a cycle ergometer (Monark 834E). VO2 during the tests was monitored breath-by-breath using an online gas analysis System (SensorMedics). WAnT30 s VO2 amounted to 67% and 73% of peak VO2 in boys and girls, respectively. By assuming extreme mechanical efficiency (ME) values of 15% and 35%, the aerobic contributions to the WAnT30s in boys and girls were between 16% and 45%. Peak VO2 and WAnT30 s power were higher in boys than in girls but there was no sex difference in the aerobic energy contribution to the WAnT30 s for the same assumed ME. The magnitude of the aerobic energy contribution to the WAnT30 s reflected plausibly a swift oxygen uptake response to maximal intensity exercise and perhaps a reduced reliance on non-oxidative metabolism in boys and girls.